Efficacy of Ultrasound in the Detection of Fractures in Comparison with the Conventional Radiography - Deepak Tolia (Asian Journal of Medical Radiological Research, 2020)
Background: Given the potential advantages of ultrasonography in remote and resource-poor settings, the validation of this tool in point-of-care fracture diagnosis could potentially allow timely and appropriate management of fractures in the community. Present study was performed with an aim to evaluate the efficacy of ultrasound in diagnosing the presence or absence of fractures in clinically suspected patients in comparison with the conventional radiography.Subjects and Methods: Sixty patients of any age group and either sex coming to emergency wing or orthopaedic outdoor or indoor and other departments at our institution with clinically suspected fractures were included for the study. Each patient was subjected to detailed history, local examination, and conventional radiography with appropriate views. This was followed by ultrasonography using real time scanner with a high frequency linear transducer in both longitudinal and transverse planes. The results of radiography and ultrasonography were compared to see their relative efficacy in the detection of fractures. Results: Both conventional radiography and ultrasonograhy detected fractures in 25 (62.5%) cases involving long bones and both modalities ruled out bony fractures in 15 (37.5%) cases (Table 1). In case of flat bone fractures, conventional radiography detected fractures in 5 (41.6%) cases and was negative in rest 7 (58.3%) cases, whereas USG detected fractures in 9 (75%) cases and was negative in 3 (25%) cases. Overall sensitivity, specificity, PPV, NPV and accuracy values of CR against USG in this present study came out to be 81.41%, 100%, 100%, 74.25% and 89.2%, respectively. Conclusion: Ultrasonographic examination might act as a substitute for radiography in detection of bony fractures, thus saving the patient from radiation exposure.